Strategi Implementasi Kompetensi Pedagogik Guru Mismatch sebagai Upaya Pengembangan Potensi Siswa di SMA N 1 Gemolong - Prabaswara, Dyatmika; Astutik, Dwi; Purwanto, Danang (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Pedagogical competence is one of the professional competencies that every teacher must have. This is due to the urgency of pedagogical competence to understand students, conduct learning, and evaluation that ensures the quality of learning outcomes. However, this condition is difficult to apply to mismatch teachers because they do not have an adequate knowledge base. As a result, learning is only done to fulfill obligations. This research aims to find out the strategies carried out by mismatch teachers at SMA N 1 Gemolong in their efforts to optimize their pedagogical abilities, especially on the indicators of mastery of materials and learning activities. Qualitative research method with case study approach was used in this research. The population of this research is teachers of SMA N 1 Gemolong. The sample of this research is teachers who experience mismatch and are selected by purposive sampling method. The results showed that teachers carried out various strategies to implement pedagogical competence in mismatch subjects, namely elaborating material, simplifying learning outcomes, seeking references to learning practices from other teachers, and developing affective actions. These efforts are made on the basis of rational choices regarding moral responsibility as a teacher objectively. These efforts are ultimately able to maintain a balance of quality between the main subjects and mismath subjects.